A política paraibana vigiada: políticos e militantes sob os olhos do SNI (1964-1985) - Soares, Maria Tereza Dantas Bezerra (2020)
This dissertation aims to identify, analyze and understand the surveillance exercised by the Serviço Nacional de Informações (SNI) over politicians and militants of left-wing organizations in the state of Paraíba, during the Brazilian military dictatorship (1964 to 1985). On a macro scale, we conducted a refined research on the documents of the Fundo SNI - Agência Recife in order to identify the political parties and left-wing organizations that worked in Paraíba and were subject of surveillance by SNI and other Information Organs (OIs). At a more personal level, we observed the surveillance of Paraiban political actors, professional politicians and activists from leftist organizations, aiming to understand how and why it occurred. Thereby, the sources used in this research are mostly from the collection of the Serviço Nacional de Informações (SNI), characterized as “sensitive documents”, because they are “sets that were created as instruments of repression” (THIESEN, 2013: 4). We also made use of testimonials given at public hearings held by the Comissão Estadual da Verdade e Preservação da Memória da Paraíba (CEVPM-PB) and documentation of the Comissão Nacional de Anistia. The research locates itself at the field of the new political history, using the concept of political culture, as exposed by Rodrigo Patto Sá Motta (2009). We also use aspects of the field theory thought by sociologist Pierre Bourdieu (1998), specifically, the concept of political field. This dissertation focuses on the History and Historical Culture areas, linked to the History and Regionalities research area